2018
DOI: 10.1002/hed.25129
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms, social anxiety, and perceived neck function in patients with head and neck cancer

Abstract: Impaired physical function and psychological distress are intertwined for patients with head and neck cancer long after completing treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…In total 33 of these articles fulfilled the eligibility criteria. In addition, two studies were included after screening the reference lists, resulting in 35 articles . These 35 articles provided results on 27 separate studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total 33 of these articles fulfilled the eligibility criteria. In addition, two studies were included after screening the reference lists, resulting in 35 articles . These 35 articles provided results on 27 separate studies.…”
Section: Resultsmentioning
confidence: 99%
“…In Table , the characteristics of the 35 included studies are described. Twenty‐one studies reported on factors associated with depression at a single time point, 10 studies on factors associated with the course of depression and four on both . Results on factors associated with depression at a single time point and the course of depression are presented separately.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations